Efficacy of drugs most commonly prescribed at functional gastrointestinal diseases (functional dyspepsia syndrome and irritable bowel syndrome) observational study results - V. T. Ivashkin; Ye. A. Poluektova; D. V. Reykhart; O. S. Shifrin; A. G. Beniashvili; O. S. Lyashenko; A. V. Belostotsky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate the frequency of prescription of motility regulators and probiotics in the functional gastrointestinal diseases. To define efficacy of these agents according to results of «7×7» questionnaire (7 symptoms per 7 days) at treatment of functional dyspepsia (FD), irritable bowel syndrome (IBS) and combination of these diseases. Material and methods. Overall 502 patients aged 18 to 65 with symptoms complying to the «Rome-III» criteria and absence of «alarm symptoms» with the preliminary diagnosis of the functional gastrointestinal disorder: IBS, FD or combination of these diseases were started. During the first visit to the doctor patient was proposed to complete «7×7» questionnaire for baseline assessment of presence and severity of symptoms typical for FD and IBS. Later all patients underwent a set of laboratory and instrumental tests required according to «Guidelines on diagnostics and treatment of the irritable bowel syndrome in adults» of the Russian gastroenterological association and Russian Association of coloproctology and to «Clinical guidelines on diagnostics and treatment of the functional dyspepsia» of the Russian gastroenterological association. After primary investigation 108 patients were excluded from the study due to diagnosis change. Primary documentation data of 11 patients were unsuitable for statistical processing. The analysis of primary documentation and results symptom assessment of 383 patients with verified diagnosis of functional gastrointestinal disease by «7×7» questionnaire was carried out. Treatment algorithms, their conformity to establish diagnosis and efficacy were analyzed as well. Results. Motility regulator trimebutine was prescribed to 258 (67,4%) patients with various diseases: 30 (60%) IBS patients, 67 (73,6%) FD patients, and 157 (64,8%) patients with combination of both disorders. Modes of treatment which included trimebutine demonstrated higher efficacy in comparison to treatment algorithms, which included antispasmodic medications with respect to relief of all symptoms (according to the «7×7» questionnaire data), except for constipation and in disorders of stool consistency (firm stool): efficacy of trimebutinecontaining moods for those symptoms was comparable to those with application of spasmolytic drugs. Probiotic agents with various content in combination to other group drugs were prescribed to 127 patients: 29 FD patients (22,3%); 20 IBS patients (14,5%), and 78 FD to IBS combination (60%). It is established that presence of probiotic in the treatment mode leads to significant reduction in main symptoms severity typical both for FD and IBS according to the «7×7» questionnaire.